1987
DOI: 10.1021/np50054a008
|View full text |Cite
|
Sign up to set email alerts
|

Potential Inhibitors of Platelet Aggregation from Plant Sources, III

Abstract: 3,4-Dihydroxybenzoic acid (DBA) was isolated from Acanthopanax senticosus as an antiplatelet aggregatory substance. This paper also reports the results of the investigations on the structural activity relationships among the various dihydroxybenzoic acid derivatives against rat platelet aggregations induced by ADP (adenosine 5'-diphosphate), AA (arachidonic acid), or collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…Previous studies have reported that PCA blocked agonistinduced platelet change such as ADP-, arachidonic acid-, or collagen-induced platelet aggregation (Yun-Choi et al, 1987;Chang and Hsu, 1992), which was not observed in our study. The effective concentration of PCA in those studies was 10 Ϫ4 to 10 Ϫ3 M, which is much higher than in our experimental system, and this high concentration range might not be easily achieved in an in vivo system.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies have reported that PCA blocked agonistinduced platelet change such as ADP-, arachidonic acid-, or collagen-induced platelet aggregation (Yun-Choi et al, 1987;Chang and Hsu, 1992), which was not observed in our study. The effective concentration of PCA in those studies was 10 Ϫ4 to 10 Ϫ3 M, which is much higher than in our experimental system, and this high concentration range might not be easily achieved in an in vivo system.…”
Section: Discussioncontrasting
confidence: 84%
“…Of those, we determined that MV is as the most effective active ingredient that increases osteoblast differentiation with activation of the Wnt/β-catenin pathway. MV is present in many plants, including the stem bark of Zanthoxylum scandens and HDT, and has been reported to have anti-platelet and anti-oxidant activity [36], [41][43]. Here, we showed that MV induces osteoblast differentiation in vitro and the oral administration of MV rescues femoral trabecular and cortical bone loss caused by OVX.…”
Section: Discussionmentioning
confidence: 60%
“…It had been reported that hot water extract of E. senticosus reduced the levels of aspartate transaminase and alanine transaminase in serum and improved histological changes of liver in carbon tetrachloride‐or acetaminophen‐induced liver injury in rats (Lin & Huang 2000). Since E. senticosus have been reported to inhibit tumour necrosis factor‐α production (Yi et al 2002) and inhibit platelet aggregation (Yun‐Choi et al 1987) it was suggested that E. senticosus may be effective in suppressing liver injury induced by D‐galactosamine/lipopolysaccharide, because tumour necrosis factor‐α and platelet activating factor are important in D‐galactosamine/lipopolysaccharide‐induced fulminant hepatic failure (Komatsu et al 1996).…”
mentioning
confidence: 99%